Exclusive Image Gallery on Human Spinal Cord Regeneration-Clinical Image-40 - Giselher Schalow (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2019)
Primary motor areas (homunculus of the brain). Note that the toes are close to urinary bladder and rectum areas.